GALECTIN-3, MMP-9 AND ST-2: BIOCHEMICAL MARKERS IN CARDIOVASCULAR DISEASES - Anak Agung Wiradewi Lestari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Galectin-3 is a reasonably stable biomarker. It can be detected even before the onset of heart failure occurs. Heart Failure (HF) is one of the complications of AMI as well as one of the major cardiovascular parameters. One study showed that elevated levels of Galectin-3 that persisted up to 3-6 months of the follow-up period in patients with heart failure were associated with a poorer prognosis. Many studies explain that the role of Galectin-3 is strong in cardiac remodeling/fibrosis and the occurrence of heart failure. Inhibition of Galectin-3 by pharmacological agents has been shown to be able to the prevent that cardiac fibrosis process, particularly in patients with advanced heart failure. Since its discovery as a gene product induced by cardiomyocyte stretch in vitro, ST2 has emerged as a powerful player with IL-33 in modulating ventricular function and remodeling via effects on apoptosis, inflammation and myocardial fibrosis. Clinically, measurement of sST2 appears promising as a biomarker for remodeling and outcome across the AHA HF Stages. Circulating levels of sST2 are strongly related to short and long-term post-discharge mortality in acute coronary syndromes and HF, as well as markers of cardiac structure and function. Current pre-clinical and clinical documentation strongly support MMP-9 as a panel member in the biomarker list to diagnose or treat the pathophysiology of post-MI ventricular remodeling and congestive heart failure. Based on the evidence provided, further prospective studies are required to assess the prognostic value of MMP-9 for post-MI remodeling, particularly in comparison with traditional markers.